Secondary battery and electronic device

By setting up protrusions on the straight and bending areas of the electrode assembly and adding sulfur oxide compounds to the electrolyte, the problems of insufficient electrolyte and interface deterioration are solved, and the circulation performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery are improved.

CN119852554APending Publication Date: 2025-04-18NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202510307346.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The electrode assembly with the winding structure in existing secondary batteries can easily lead to insufficient electrolyte and poor infiltration during charging and discharging, resulting in deterioration of the interface, affecting circulation and safety performance.

Method used

A plurality of first and second protrusions are respectively arranged on the straight and bending regions of the electrode assembly, and the electrolyte contains sulfur oxide compounds, the composition of the electrolyte and the structure of the electrode sheet are optimized to improve the wettability and interface quality of the electrolyte.

Benefits of technology

By improving the wetting properties of the electrolyte, reducing the interface resistance of the electrode sheet, extending the cycle life of the secondary battery, and improving low-temperature discharge performance and high-temperature storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852554A_ABST
    Figure CN119852554A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, the secondary battery comprises an electrode assembly of a winding structure and an electrolyte, the electrode assembly comprises a pole piece, the electrode assembly comprises a straight area and a bending area, a plurality of first protrusions are arranged on the pole piece in the straight area, a plurality of second protrusions are arranged on the pole piece in the bending area, and the first protrusions and the second protrusions are arranged along the thickness direction of the pole piece. The average height of the plurality of first protrusions is H1 [mu] m, the average height of the plurality of second protrusions is H2 [mu] m, 1.5 < = H2 / H1 < = 5, 5 < = H1 < = 40, and the electrolyte contains a sulfur oxide compound. Through the arrangement, the infiltration of the electrolyte on the electrode assembly is improved, the interface of the electrode assembly is improved, and the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] Lithium-ion batteries have the advantages of good rate performance, light weight, long cycle life, no memory effect and good stability. They are the most widely used energy storage and power products under current technical conditions.

[0003] At present, the electrode assemblies in larger secondary batteries are mostly of a wound structure. For the electrode assemblies with a wound structure, hot pressing is required after winding to fix the electrode assemblies to prevent them from being poorly packed in the packaging bag. However, in this case, the electrolyte is not easy to enter the interior of the electrode assembly, which may easily lead to insufficient electrolyte inside the electrode assembly, poor wetting, and ultimately deterioration of the interface, affecting the cycle performance of the secondary battery and even causing lithium deposition, affecting the safety performance of the secondary battery. Summary of the invention

[0004] The purpose of the present application is to provide a secondary battery and an electronic device to improve the wetting of the electrolyte into the electrode assembly, improve the interface of the electrode assembly, and improve the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery.

[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0006] A first aspect of the present application provides a secondary battery, comprising an electrode assembly of a wound structure and an electrolyte, the electrode assembly comprising a pole piece, the electrode assembly comprising a straight area and a bent area, a plurality of first protrusions are arranged on the pole piece in the straight area, a plurality of second protrusions are arranged on the pole piece in the bent area, along the thickness direction of the pole piece, the average height of the plurality of first protrusions is H1μm, the average height of the plurality of second protrusions is H2μm, 1.5≤H2 / H1≤5, preferably, 2≤H2 / H1≤4; 5≤H1≤40, preferably, 5≤H1≤20; the electrolyte contains sulfur oxides. By respectively arranging protrusions on the pole pieces in the straight area and the bent area, the protrusions play a supporting role during the winding process and the circulation process of the pole piece, thereby increasing the gap between the pole piece layers; when the electrolyte contains sulfur oxide compounds, the sulfur oxide compounds can form a stable solid electrolyte interface film containing sulfur-oxygen bonds on the surface of the pole piece and the electrolyte in preference to other solvents, and at the same time, it is beneficial to improve the wetting of the electrolyte on the electrode assembly, thereby reducing the occurrence of side reactions between the pole piece and the electrolyte, reducing the generation of interface gas, thereby reducing the interface resistance of the pole piece, improving the interface of the electrode assembly, and improving the cycle performance of the secondary battery; while improving the wettability of the electrolyte to the pole piece, the tightness between the pole piece layers in the straight area is maintained, the interface resistance is reduced, the risk of local overheating of the pole piece is reduced, especially reducing the heat accumulation at the protrusions of the pole piece, and also optimizing the electron transmission path, thereby improving the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery.

[0007] In some embodiments of the present application, 20≤H2≤80. Providing the second protrusion in the above height range on the pole piece in the bending region is conducive to further improving the cycle performance of the secondary battery, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0008] In some embodiments of the present application, along the thickness direction of the pole piece, the diameter of the maximum circumscribed circle of the outer contour of the orthographic projection of the first protrusion on the pole piece is R1 mm, the diameter of the maximum circumscribed circle of the outer contour of the orthographic projection of the second protrusion on the pole piece is R2 mm, 0.3≤R1≤10, 0.3≤R2≤10. By regulating the values ​​of R1 and R2 within the above range, the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery are improved, and the processing performance of the secondary battery is also taken into account.

[0009] In some embodiments of the present application, along the thickness direction of the pole piece, the first protrusion and the second protrusion are located on the same side of the pole piece; or, the first protrusion and the second protrusion are located on different sides of the pole piece. Through the above arrangement, the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery are improved. In addition, the operability of setting different protrusions on the pole piece is also improved, which is conducive to reducing the production cost of the secondary battery while meeting the mass production manufacturability.

[0010] In some embodiments of the present application, the pole piece is a positive pole piece. When the pole piece is a positive pole piece, while improving the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery, it is beneficial to reduce the risk of active material loss due to excessive powder loss during pole piece processing and thus reduce the energy density of the secondary battery.

[0011] In some embodiments of the present application, the electrolyte includes propylene carbonate and propyl propionate. Based on the mass of the electrolyte, the mass percentage of propylene carbonate is A1, and the mass percentage of propyl propionate is A2. 2.5%≤A1≤15%, preferably, 4%≤A1≤12%; 20%≤A2≤40%; preferably, 30%≤A2≤40%. In some embodiments of the present application, it satisfies one of the following conditions: (1) 22.5%≤A1+A2<43%, 20≤H2<60; (2) 43%≤A1+A2≤55%, 60≤H2≤80. By selecting an electrolyte including propylene carbonate and propyl propionate, and adjusting the values ​​of A1 and A2 within the above range, propyl propionate and propylene carbonate work synergistically to improve the cycle performance, low temperature discharge performance and high temperature storage performance.

[0012] In some embodiments of the present application, the sulfur oxide in the electrolyte includes at least one of 1,3-propane sultone, disulfate or vinyl sulfate. Preferably, the sulfur oxide includes 1,3-propane sultone; based on the mass of the electrolyte, the mass percentage of the sulfur oxide is B, 0.5%≤B≤4%; preferably, 0.6%≤B≤2.8%. In some embodiments of the present application, it satisfies one of the following conditions: (1) 0.5%≤B<2%, 20≤H2<60; (2) 2%≤B≤4%, 60≤H2≤80. By selecting an electrolyte including a sulfur oxide and adjusting the value of B within the above range, and matching the first protrusion and the second protrusion on the electrode sheet, the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery are improved.

[0013] In some embodiments of the present application, the electrolyte includes a nitrile additive, and the nitrile additive includes at least one of malononitrile, succinonitrile, adiponitrile, terephthalonitrile, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-di(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether or diethylene glycol di(2-cyanoethyl) ether. Based on the mass of the electrolyte, the mass percentage of the nitrile additive is C, 0.8%≤C≤4.5%. In some embodiments of the present application, it satisfies one of the following conditions: (1) 0.8%≤C<3%, 20≤H2<60; (2) 3%≤C≤4.5%, 60≤H2≤80. By selecting an electrolyte including a nitrile additive and adjusting the value of C within the above range, and matching the first protrusion and the second protrusion on the electrode sheet, the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery are improved.

[0014] In some embodiments of the present application, the electrolyte further includes fluorobenzene, and the mass percentage of fluorobenzene is D based on the mass of the electrolyte, 2%≤D≤8%. In some embodiments of the present application, it satisfies one of the following conditions: (1) 2%≤D<5%, 20≤H2<60; (2) 5%≤D≤8%, 60≤H2≤80. By selecting an electrolyte including fluorobenzene and adjusting the value of D within the above range, in combination with the first protrusion and the second protrusion on the electrode sheet, the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery are improved.

[0015] The second aspect of the present application provides an electronic device, which includes the secondary battery in any one of the above embodiments. Therefore, the electronic device provided by the present application has good performance.

[0016] Beneficial effects of this application:

[0017] The present application provides a secondary battery and an electronic device, wherein the secondary battery comprises an electrode assembly of a winding structure and an electrolyte, wherein the electrode assembly comprises a pole piece, and the electrode assembly comprises a straight region and a bent region, wherein a plurality of first protrusions are arranged on the pole piece in the straight region, and a plurality of second protrusions are arranged on the pole piece in the bent region, wherein along the thickness direction of the pole piece, the average height of the plurality of first protrusions is H1μm, and the average height of the plurality of second protrusions is H2μm, 1.5≤H2 / H1≤5, 5≤H1≤40; and the electrolyte comprises sulfur oxides. By arranging different protrusions at different positions of the pole piece, the protrusions can play a supporting role during the winding process, so that a gap is formed between the pole piece layers of the electrode assembly, and the sulfur oxides in the electrolyte are matched, thereby improving the transmission capacity of the electrolyte inside the electrode assembly, improving the interface of the electrode assembly, and improving the cycle performance, low-temperature discharge performance, and high-temperature storage performance of the secondary battery.

[0018] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.

[0020] Figure 1 A schematic diagram of an electrode assembly of a wound structure in one embodiment of the present application;

[0021] Figure 2 It is a schematic diagram of a partial structure of a positive electrode sheet along its thickness direction after unfolding in another embodiment of the present application;

[0022] Figure 3 This is a schematic diagram of a wound structure electrode assembly in another embodiment of the present application.

[0023] Reference numerals: electrode assembly 001 ; positive electrode sheet 10 ; negative electrode sheet 20 ; separator 30 ; straight area 0011 ; bending area 0012 ; first protrusion 101 ; second protrusion 102 . DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0025] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0026] In the prior art, the electrode assemblies in the larger secondary batteries are mostly wound structures. For the electrode assemblies with wound structures, due to the existence of internal stress, the internal layers of the electrode assemblies are relatively close, the wettability of the electrode assemblies is poor, and the electrode assemblies expand during the charge and discharge process, and the interlayer extrusion is further aggravated, which can easily lead to insufficient electrolyte in the electrode assemblies, especially the internal electrolyte, poor wettability, interface deterioration in some areas, and even lithium precipitation. In order to solve the above problems, it is necessary to create gaps between the layers of the electrode assemblies. At present, the following methods are commonly used to create gaps: (1) sticking adhesive tape at specific positions of the electrode sheets of the electrode assemblies to support the formation of pores; however, due to the existence of the adhesive tape, the thickness difference of the electrode assemblies is increased, and the volume energy density of the secondary battery is lost to a certain extent; (2) coating some glue soluble in electrolyte on the surface of the electrode sheets of the electrode assemblies to form pores; but the improvement effect is effective, and there are other side effects on the performance of the secondary battery; (3) using a thickened diaphragm to enhance the liquid storage performance of the diaphragm; but it will increase the thickness of the electrode assembly itself and reduce the energy density of the secondary battery. Based on this, the present application provides a secondary battery and an electronic device, which improve the electrolyte infiltration into the electrode assembly, improve the interface of the electrode assembly, and improve the cycle performance, low-temperature discharge performance, and high-temperature storage performance of the secondary battery while taking into account the energy density of the secondary battery. The specific technical solution is as follows:

[0027] A first aspect of the present application provides a secondary battery, the secondary battery comprising an electrode assembly of a winding structure and an electrolyte, the electrode assembly comprising a pole piece, the electrode assembly comprising a straight region and a bent region, a plurality of first protrusions are arranged on the pole piece in the straight region, a plurality of second protrusions are arranged on the pole piece in the bent region, along the thickness direction of the pole piece, the average height of the plurality of first protrusions is H1 μm, the average height of the plurality of second protrusions is H2 μm, 1.5≤H2 / H1≤5, preferably, 2≤H2 / H1≤4, for example, H2 / The value of H1 can be 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5 or a range consisting of any two of the values ​​therein; 5≤H1≤40, preferably, 5≤H1≤20, for example, the value of H1 can be 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40 or a range consisting of any two of the values ​​therein; the electrolyte contains sulfur oxides.

[0028] In the present application, the electrode sheet may be a positive electrode sheet and / or a negative electrode sheet. When the electrode sheet is a positive electrode sheet, the electrode assembly further includes another electrode sheet with opposite polarity to that of the electrode sheet, namely, a negative electrode sheet. When the electrode sheet is a negative electrode sheet, the electrode assembly further includes another electrode sheet with opposite polarity to that of the electrode sheet, namely, a positive electrode sheet. For ease of understanding, it is defined that when the electrode assembly is in an unfolded state, its own length direction is the X direction, its own width direction is the Y direction, and its own thickness direction is the Z direction. It can be understood that when the positive electrode sheet, the negative electrode sheet and the separator are in an unfolded state, their own length direction, width direction and thickness direction are the same as those of the electrode assembly, and the winding direction of the electrode assembly is the W direction. Exemplarily, the electrode sheet is a positive electrode sheet, such as Figure 1 and Figure 2 As shown, the electrode assembly 001 includes a positive electrode sheet 10, a negative electrode sheet 20 and a separator 30. The electrode assembly 001 includes a straight area 0011 and two bending areas 0012 connected to the straight area 0011. A plurality of first protrusions 101 are provided on the positive electrode sheet 10 in the straight area 0011, and a plurality of second protrusions 102 are provided on the positive electrode sheet 10 in the bending area 0012. Along the thickness direction Z direction of the positive electrode sheet 10, the average height of the plurality of first protrusions 101 is H1μm, and the average height of the plurality of second protrusions 102 is H2μm. The number, size, spacing, height, etc. of the first protrusions and the second protrusions in the figure are only for exemplary illustration, and the present application is not limited thereto. In the present application, the above-mentioned "multiple" refers to two or more.

[0029] When the value of H2 / H1 is too high, that is, higher than the upper limit value of the present application, the height difference between the protrusion on the pole piece in the bending zone and the protrusion on the pole piece in the straight zone is too large, which increases the stress gradient between the bending zone and the straight zone, easily leading to interface peeling between the material layer and the current collector, affecting the electron transmission of the pole piece, and thereby reducing the cycle performance and low-temperature discharge performance of the secondary battery; when the value of H2 / H1 is too low, that is, lower than the lower limit value of the present application, the height difference between the protrusion on the pole piece in the bending zone and the protrusion on the pole piece in the straight zone is too small, the height of the protrusion on the pole piece in the bending zone is insufficient, and the bending stress cannot be effectively dispersed. Furthermore, when the value of H2 / H1 is less than 1, it is easy to cause interruption of the electron transmission path in the local area or poor contact, resulting in uneven lithium ion embedding / ejection, and reducing the cycle performance and low-temperature discharge performance of the secondary battery. When the value of H1 is too high, that is, higher than the upper limit value of this application, the first protrusion is higher, and the corresponding second protrusion is also higher. The gap between the electrode layers is larger, and the electrolyte bridge is easily broken between the layers of some electrode sheets, resulting in an increase in electrochemical impedance during the cycle of the secondary battery. The resistance to ion conduction during the cycle is greater, which reduces the cycle performance and low-temperature discharge performance of the secondary battery; when the value of H1 is too low, that is, lower than the lower limit value of this application, the first protrusion is lower, and the corresponding second protrusion is also lower, which reduces the effective contact area between the electrode and the current collector, resulting in obstruction of the electron transmission path and an increase in the overall internal resistance. At this time, the electrode assembly is prone to local overheating, resulting in a decrease in the thermal safety performance of the secondary battery, and the cycle performance and low-temperature discharge performance are also affected. By respectively arranging protrusions on the pole pieces in the straight area and the bent area, the protrusions play a supporting role during the winding process and the cycle process of the pole piece, so that the gap between the pole piece layers is increased, which is beneficial to improving the infiltration of the electrolyte into the electrode assembly, thereby improving the interface of the electrode assembly and improving the cycle performance of the secondary battery; further, the protrusions arranged on the pole pieces in the straight area and the bent area have different heights, and the values ​​of H2 / H1 and H1 are adjusted within the above range. During the charge and discharge process, the bent area of ​​the electrode assembly has a periodic bending stress compared with the straight area of ​​the electrode assembly, and the bending area is subjected to the periodic bending stress. Setting a higher protrusion on the pole piece is beneficial to reducing the impact of the stress in the bending zone on the electrode assembly. In addition, the embedding and extraction of lithium ions can easily cause the volume of the pole piece to expand. Setting a high protrusion on the pole piece in the bending zone is beneficial to reserving expansion space, reducing purple spots and lithium precipitation after the electrolyte in the secondary battery is reduced. Problems such as this are beneficial to further improve the cycle performance of the secondary battery, especially in low-temperature tests, which can be more conducive to maintaining the normal migration rate of lithium ions during charge and discharge, thereby improving the low-temperature charge and discharge performance of the secondary battery; because the ion migration ability decreases at low temperatures, it is easier to deposit lithium on the surface of the pole piece.The low protrusions on the straight-area electrode are beneficial for improving the wettability of the electrolyte to the electrode while maintaining the tightness between the layers of the electrode in the straight-area, thereby reducing the interface resistance. When sulfur oxide compounds are added to the electrolyte, the stable solid electrolyte interface film containing sulfur oxide bonds formed is more conducive to reducing the resistance at the interface between the electrode and the electrolyte, especially the ion transmission at the protrusions will be smoother, reducing the risk of local overheating at the protrusions of the electrode, and also optimizing the electron transmission path. The overall internal resistance of the electrode assembly is reduced, thereby improving the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery.

[0030] In some embodiments of the present application, 20≤H2≤80. For example, the value of H2 can be 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50, 52, 55, 58, 60, 62, 65, 68, 70, 72, 75, 78, 80, or a range consisting of any two of the values. By setting a second protrusion in the above-mentioned height range on the pole piece in the bending area, the second protrusion plays a supporting role during the winding process and the circulation process of the pole piece, which is beneficial to increase the gap between the pole piece layers in the bending area, improve the infiltration of the electrolyte into the electrode assembly, thereby improving the interface of the electrode assembly and improving the cycle performance of the secondary battery; during the charging and discharging process, the bending area of ​​the electrode assembly has a periodic bending stress compared to the straight area of ​​the electrode assembly. Regulating the value of H2 within the above-mentioned range is beneficial to reducing the influence of the bending area stress on the electrode assembly. In addition, the embedding and extraction of lithium ions can easily cause the volume of the pole piece to expand. The high protrusion set on the pole piece in the bending area is beneficial to reserving expansion space, reducing the risk of peeling between the pole piece layers, and is beneficial to further improving the cycle performance of the secondary battery, thereby improving the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery.

[0031] In some embodiments of the present application, along the thickness direction of the pole piece, the diameter of the maximum circumscribed circle of the outer contour of the positive projection of the first protrusion on the pole piece is R1 mm, and the diameter of the maximum circumscribed circle of the outer contour of the positive projection of the second protrusion on the pole piece is R2 mm, 0.3≤R1≤10, for example, the value of R1 can be 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, 7, 7.2, 7.5, 7.8, 8, 8.2, 8.5, 8.8, 9, 9.2, 9.5, 9.8, 10 or a range of any two of the values. 0.3≤R2≤10, for example, the value of R2 can be 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, 7, 7.2, 7.5, 7.8, 8, 8.2, 8.5, 8.8, 9, 9.2, 9.5, 9.8, 10 or a range consisting of any two of the values. For example, Figure 2 As shown, along the thickness direction Z direction of the positive electrode sheet 10, the diameter of the maximum circumscribed circle of the outer contour of the orthographic projection of the first protrusion 101 on the positive electrode sheet 10 is R1 mm, and the diameter of the maximum circumscribed circle of the outer contour of the orthographic projection of the second protrusion 102 on the positive electrode sheet 10 is R2 mm. By adjusting the values ​​of R1 and R2 within the above range, it is beneficial to improve the infiltration of the electrolyte into the electrode assembly, thereby improving the circulation interface of the electrode assembly and improving the cycle performance of the secondary battery; at the same time, it is beneficial to reduce the risk of delamination of the material layer and the current collector interface caused by local stress concentration of the electrode sheet, maintain the electronic path between the active material and the current collector, and increase the electrolyte retention, which is beneficial to form a continuous and balanced electron and ion transmission network during the cycle process, reduce the internal resistance of the secondary battery, thereby improving the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery, and also taking into account the processing performance of the secondary battery. In the present application, the shape of the protrusion may be a regular sphere, a sphere with different sphericity, or other shapes. When measuring the diameter of a non-regular spherical protrusion, the equivalent diameter of the distance between the two farthest points may be measured as the diameter.

[0032] In some embodiments of the present application, along the thickness direction of the pole piece, the first protrusion and the second protrusion are located on the same side of the pole piece; or, the first protrusion and the second protrusion are located on different sides of the pole piece. Figure 1 As shown, along the thickness direction Z of the positive electrode sheet 10, the first protrusion 101 and the second protrusion 102 are located on the same side of the positive electrode sheet 10. Figure 3 As shown, along the thickness direction Z direction of the positive electrode sheet 10, the first protrusion 101 and the second protrusion 102 are located on different sides of the positive electrode sheet 10. Through the above-mentioned arrangement, during the winding process and the circulation process of the electrode sheet, the protrusion plays a supporting role, so that the gap between the electrode sheet layers is increased, which is conducive to improving the infiltration of the electrolyte into the electrode assembly, thereby improving the circulation interface of the electrode assembly and improving the circulation performance of the secondary battery; at the same time, it is conducive to maintaining the tightness between the electrode sheet layers, reducing the interface resistance, reducing the risk of local overheating of the electrode sheet, and optimizing the electron transmission path, thereby improving the circulation performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery. In addition, the operability of setting different protrusions on the electrode sheet is also improved, which is conducive to reducing the production cost of the secondary battery while meeting the mass production manufacturability.

[0033] In some embodiments of the present application, the pole piece is a positive pole piece. When the pole piece is a positive pole piece, while improving the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery, it is beneficial to reduce the difficulty of processing the pole piece during processing, and also reduce the risk of excessive powder loss during pole piece processing, resulting in loss of active materials and thus reducing the energy density of the secondary battery.

[0034] In some embodiments of the present application, the electrolyte includes propylene carbonate and propyl propionate, based on the mass of the electrolyte, the mass percentage of propylene carbonate is A1, the mass percentage of propyl propionate is A2, 2.5%≤A1≤15%, preferably, 4%≤A1≤12%, for example, the value of A1 can be 2.5%, 2.8%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or a range consisting of any two of them; 20%≤A2≤40%; preferably, 30%≤A2≤40%, for example, the value of A2 can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40% or a range consisting of any two of them. Propylene carbonate has a high dielectric constant and low viscosity, and its low temperature performance is good; propyl propylene has good stability, can maintain stable performance in a wide temperature range, and its high temperature storage stability performance is good. By selecting an electrolyte including propylene carbonate and propyl propylene, and regulating the values ​​of A1 and A2 within the above range, propyl propylene and propylene carbonate work synergistically, which is beneficial to improve the low-temperature performance of the secondary battery while also taking into account the high-temperature performance; combined with the first protrusion and the second protrusion on the electrode piece, the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery are improved.

[0035] In some embodiments of the present application, 22.5%≤A1+A2<43%, 20≤H2<60, for example, 22.5%≤A1+A2<43%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values. By adjusting the value of A1+A2 in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0036] In some embodiments of the present application, 43%≤A1+A2≤55%, 60≤H2≤80, for example, 43%≤A1+A2≤55%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of these values. By adjusting the value of A1+A2 in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0037] In some embodiments of the present application, the following conditions are satisfied: (1) 22.5%≤A1+A2<43%, 20≤H2<60, for example, 22.5%≤A1+A2<43%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values ​​therein; (2) 43%≤A1+A2≤55%, 60≤H2≤80, for example, 43%≤A1+A2≤55%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of the values ​​therein. By adjusting the value of A1+A2 within different ranges, when the value of H2 is within the above range, the protruding structure on the electrode piece and the electrolyte cooperate with each other, which is beneficial to accelerate the infiltration of the electrolyte into the electrode piece and further improve the wetting performance of the electrolyte to the electrode assembly, thereby improving the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery.

[0038] In some embodiments of the present application, the sulfur oxide in the electrolyte includes at least one of 1,3-propane sultone, disulfate or vinyl sulfate, preferably, the sulfur oxide includes 1,3-propane sultone; based on the mass of the electrolyte, the mass percentage of the sulfur oxide is B, 0.5%≤B≤4%; preferably, 0.6%≤B≤2.8%. For example, the value of B can be 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4% or a range consisting of any two of the values. Sulfur oxides have high oxidation stability and large dielectric constants, showing good stability to high-voltage positive electrodes. For example, its oxidation stability can reach more than 5V, and it has good stability when applied to high-voltage lithium batteries. In addition, the dielectric constant of sulfur oxide compounds is greater than 40, which helps to form a stable SEI film and a positive electrode electrolyte interface (CEI) film, thereby protecting the positive and negative electrode materials of the secondary battery. By selecting an electrolyte including sulfur oxide compounds and adjusting the value of B within the above range, it is beneficial to improve the thermal safety performance of the secondary battery; combined with the first protrusion and the second protrusion on the electrode sheet, the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery are improved.

[0039] In some embodiments of the present application, 0.5%≤B<2%, 20≤H2<60, for example, 0.5%≤B<2%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values. By adjusting the value of B in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0040] In some embodiments of the present application, 2%≤B≤4%, 60≤H2≤80, for example, 2%≤B≤4%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of these values. By adjusting the value of B in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0041] In some embodiments of the present application, the following conditions are satisfied: (1) 0.5% ≤ B < 2%, 20 ≤ H2 < 60, for example, 0.5% ≤ B < 2%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values; (2) 2% ≤ B ≤ 4%, 60 ≤ H2 ≤ 80, for example, 2% ≤ B ≤ 4%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of the values. When the value of B is adjusted to be within different ranges, the value of H2 is within the above range, and the protruding structure on the electrode piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the electrode piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0042] In some embodiments of the present application, the electrolyte includes nitrile additives, and the nitrile additives include at least one of malononitrile, succinonitrile, adiponitrile, terephthalonitrile, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether or diethylene glycol di(2-cyanoethyl) ether, and the mass percentage of the nitrile additives is C based on the mass of the electrolyte, 0.8%≤C≤4.5%. For example, the value of C can be 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5% or a range composed of any two of the numerical values. Nitrile additives are applied to the electrolyte of secondary batteries as additives, which are beneficial to improve the stability of the positive electrode side of the secondary battery under high and low pressure and high temperature. By selecting an electrolyte including nitrile additives and adjusting the C value within the above range, it is beneficial to improve the thermal safety performance of the secondary battery; by combining the first protrusion and the second protrusion on the electrode piece, the cycle performance, low-temperature discharge performance and high-temperature storage performance of the secondary battery are improved.

[0043] In some embodiments of the present application, 0.8%≤C<3%, 20≤H2<60, for example, 0.8%≤C<3%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values. By adjusting the value of C in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0044] In some embodiments of the present application, 3%≤C≤4.5%, 60≤H2≤80, for example, 3%≤C≤4.5%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of these values. By adjusting the value of C in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0045] In some embodiments of the present application, the following conditions are satisfied: (1) 0.8% ≤ C < 3%, 20 ≤ H2 < 60, for example, 0.8% ≤ C < 3%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values; (2) 3% ≤ C ≤ 4.5%, 60 ≤ H2 ≤ 80, for example, 3% ≤ C ≤ 4.5%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of the values. By adjusting the value of C in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0046] In some embodiments of the present application, the electrolyte also includes fluorobenzene, and the mass percentage of fluorobenzene is D based on the mass of the electrolyte, 2%≤D≤8%. For example, the value of D can be 2%, 2.5%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 5.8%, 6%, 6.2%, 6.5%, 6.8%, 7%, 7.2%, 7.5%, 8% or a range consisting of any two of the values. Fluorobenzene is used as an additive in the electrolyte of the secondary battery, which helps to form a more stable and uniform SEI film, while forming a tight structural layer without increasing impedance, which helps to reduce the risk of further decomposition of the electrolyte, improve the stability of the electrolyte, and thus improve the cycle performance of the secondary battery. By selecting an electrolyte including fluorobenzene and regulating the value of D within the above range, it is beneficial to improve the thermal safety performance of the secondary battery; with the first protrusion and the second protrusion on the pole piece, the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery are improved.

[0047] In some embodiments of the present application, 2%≤D<5%, 20≤H2<60, for example, 2%≤D<5%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values. By adjusting the value of D in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0048] In some embodiments of the present application, 5%≤D≤8%, 60≤H2≤80, for example, 5%≤D≤8%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of these values. By adjusting the value of D in different ranges, the value of H2 is within the above range, and the protruding structure on the pole piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the pole piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0049] In some embodiments of the present application, the following conditions are satisfied: (1) 2% ≤ D < 5%, 20 ≤ H2 < 60, for example, 2% ≤ D < 5%, the value of H2 can be 20, 25, 30, 35, 40, 45, 50, 55, 58, 59 or a range consisting of any two of the values; (2) 5% ≤ D ≤ 8%, 60 ≤ H2 ≤ 80, for example, 5% ≤ D ≤ 8%, the value of H2 can be 60, 62, 65, 68, 70, 72, 75, 78, 80 or a range consisting of any two of the values. When the value of D is adjusted to be within different ranges, the value of H2 is within the above range, and the protruding structure on the electrode piece cooperates with the electrolyte, which is conducive to accelerating the infiltration of the electrolyte into the electrode piece, further improving the infiltration performance of the electrolyte into the electrode assembly, thereby improving the cycle performance, low temperature discharge performance and high temperature storage performance of the secondary battery.

[0050] In the present application, the electrolyte also includes a lithium salt and a non-aqueous solvent. The lithium salt may include at least one of LiPF6, LiNO3, LiBF4, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or lithium difluoroborate. The present application does not particularly limit the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt is 8% to 15%.

[0051] The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorocarbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or butylene carbonate. Fluorinated carbonate compounds may include but are not limited to at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. Exemplarily, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent is 13.5% to 91.5%.

[0052] In some embodiments of the present application, the electrolyte may include a lithium salt, a sulfur oxide compound and a non-aqueous solvent, the mass percentage of the lithium salt and the sulfur oxide compound is as described above, and the mass percentage of the non-aqueous solvent is 81% to 91.5%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0053] In some embodiments of the present application, the electrolyte may include lithium salt, ethylene carbonate, propyl propionate, sulfur oxide and non-aqueous solvent, the mass percentage of lithium salt, ethylene carbonate, propyl propionate and sulfur oxide is as described above, and the mass percentage of non-aqueous solvent is 26% to 69%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0054] In some embodiments of the present application, the electrolyte may include a lithium salt, a sulfur oxide compound, a nitrile additive and a non-aqueous solvent, the mass percentage of the lithium salt, the sulfur oxide compound and the nitrile additive is as described above, and the mass percentage of the non-aqueous solvent is 76.5% to 90.7%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0055] In some embodiments of the present application, the electrolyte may include a lithium salt, a sulfur oxide, fluorobenzene and a non-aqueous solvent, the mass percentages of the lithium salt, the sulfur oxide and the fluorobenzene are as described above, and the mass percentage of the non-aqueous solvent is 73% to 89.5%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0056] In some embodiments of the present application, the electrolyte may include lithium salt, ethylene carbonate, propyl propionate, sulfur oxide, nitrile additives and non-aqueous solvents, the mass percentage of lithium salt, ethylene carbonate, propyl propionate, sulfur oxide and nitrile additives is as described above, and the mass percentage of non-aqueous solvent is 21.5% to 68.2%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0057] In some embodiments of the present application, the electrolyte may include lithium salt, ethylene carbonate, propyl propionate, sulfur oxide, fluorobenzene and non-aqueous solvent, the mass percentage of lithium salt, ethylene carbonate, propyl propionate, sulfur oxide and fluorobenzene is as described above, and the mass percentage of non-aqueous solvent is 18% to 67%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0058] In some embodiments of the present application, the electrolyte may include lithium salt, sulfur oxide, nitrile additive, fluorobenzene and non-aqueous solvent, the mass percentage of lithium salt, sulfur oxide, nitrile additive and fluorobenzene is as described above, and the mass percentage of non-aqueous solvent is 68.5% to 88.7%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0059] In some embodiments of the present application, the electrolyte may include lithium salt, ethylene carbonate, propyl propionate, sulfur oxide, nitrile additive, fluorobenzene and non-aqueous solvent, the mass percentage of lithium salt, ethylene carbonate, propyl propionate, sulfur oxide, nitrile additive and fluorobenzene is as described above, and the mass percentage of non-aqueous solvent is 13.5% to 66.2%. The secondary battery including the above electrolyte has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0060] In the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode current collector, as long as the purpose of this application can be achieved, for example, it can include aluminum foil, aluminum alloy foil or composite current collector (such as aluminum-carbon composite current collector). This application has no special restrictions on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of this application can be achieved. For example, the thickness of the positive electrode current collector is 5μm to 20μm, and the thickness of the positive electrode material layer is 30μm to 120μm. The positive electrode material layer includes positive electrode active materials. The present application has no particular restrictions on the positive electrode active materials, as long as the purpose of the present application can be achieved. For example, the positive electrode active materials may include but are not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. In the present application, the positive electrode active material may also include non-metallic elements, for example, non-metallic elements include at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur. In the present application, the positive electrode material layer may also include a binder and a conductive agent. The present application has no particular restrictions on the type of binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The present application has no particular restrictions on the type of conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.The present application has no particular restriction on the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.

[0061] In the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector. For example, the composite current collector can be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc. The present application has no particular restrictions on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm, and the thickness of the negative electrode material layer is 30 μm to 120 μm. The negative electrode material layer includes a negative electrode active material. The present application has no particular restrictions on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy. Optionally, the negative electrode material layer may further include a conductive agent and a binder. The present application has no particular restriction on the type of conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may be of the same type as the conductive agent in the above-mentioned positive electrode material layer. The present application has no particular restriction on the type of binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the binder in the negative electrode material layer may be of the same type as the binder in the above-mentioned positive electrode material layer. The present application has no particular restriction on the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode material layer, as long as the purpose of the present application can be achieved.

[0062] In the present application, the secondary battery also includes a diaphragm. The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or at least one of aramid. The type of diaphragm may include at least one of a woven film, a non-woven film, a microporous film, a composite film, a rolled film or a spun film. In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application has no particular restrictions on inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene). In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.

[0063] The secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0064] The present application has no particular restrictions on secondary batteries, which may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery, etc.

[0065] The present application has no particular restrictions on the preparation method of the secondary battery, as long as the purpose of the present application can be achieved. For example, the preparation method of the secondary battery includes but is not limited to the following steps: determining the pole piece with the first protrusion and the second protrusion, placing the prepared positive pole piece, diaphragm, negative pole piece, and diaphragm in order, winding them in advance, determining the straight area and the bending area of ​​the electrode assembly, respectively setting the first protrusion and the second protrusion on the determined pole piece in the straight area and the bending area, then winding to obtain the electrode assembly, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it, and obtaining the secondary battery.

[0066] The present application does not particularly limit the method of respectively setting the first protrusion and the second protrusion on the pole piece in the straight area and the bending area. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, an embossing process can be used, that is, an embossing roller and a rubber roller are used to respectively set the first protrusion and the second protrusion on the pole piece in the straight area and the bending area. Along the thickness direction of the pole piece, the shape of the first protrusion and the second protrusion on the pole piece can be regulated by the shape of the stainless steel needle on the embossing roller. The average height H1 of the first protrusion and the average height H2 of the second protrusion can be regulated by the specifications of the stainless steel needle on the embossing roller. The diameter R1 of the maximum circumscribed circle of the outer contour of the orthographic projection of the first protrusion on the pole piece and the diameter R2 of the maximum circumscribed circle of the outer contour of the orthographic projection of the second protrusion on the pole piece can be regulated by the specifications of the stainless steel needle on the embossing roller.

[0067] The second aspect of the present application provides an electronic device, which includes the secondary battery in any one of the above embodiments. Therefore, the electronic device provided by the present application has good performance.

[0068] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0069] Example

[0070] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0071] Test methods and equipment:

[0072] Tests for H1, H2, R1, R2:

[0073] At an ambient temperature of 25°C, the lithium-ion batteries of the embodiments and comparative examples were discharged at a constant current of 0.2C to 2.8V and then disassembled to obtain electrode assemblies. The straight area and the bending area of ​​the electrode assembly were observed with the naked eye to determine that the electrode piece with a protrusion on the surface was the target electrode piece, and the target electrode piece regions located in the straight area and the bending area were determined. Among them, the protrusion set on the target electrode piece in the straight area was the first protrusion, and the protrusion set on the target electrode piece in the bending area was the second protrusion.

[0074] The target electrode was taken out and soaked in dimethyl carbonate (DMC) for 20 minutes. Then, the target electrode was placed in an oven and dried at 80°C for 12 hours to obtain a test sample of the target electrode.

[0075] A scanning electron microscope (SEM) is used to observe the surface of the test sample of the target pole piece, that is, along the thickness direction of the target pole piece, the plane formed by the length and width directions of the target pole piece after it is unfolded is measured. Due to the height difference between the height of the protrusion itself and the surface of the material layer, it can be seen that there is a relatively obvious color difference on the surface of the pole piece. The protrusion has a projected aperture on the surface of the pole piece, which can be used to distinguish the protrusion from the material layer of the target pole piece.

[0076] Select any 5 apertures on the target pole piece in the straight area, measure the diameter of the maximum circumscribed circle of the outer contour of each aperture, and take the average value, which is the diameter R1 of the maximum circumscribed circle of the outer contour of the orthographic projection of the first protrusion on the pole piece. Select any 5 apertures on the target pole piece in the bent area, measure the diameter of the maximum circumscribed circle of the outer contour of each aperture, and take the average value, which is the diameter R2 of the maximum circumscribed circle of the outer contour of the orthographic projection of the second protrusion on the pole piece. When the protrusion is an irregular shape, the equivalent diameter is used, that is, the distance between the two farthest points on the orthographic projection is measured.

[0077] The target pole piece is ion polished along the length direction and thickness direction of the unfolded target pole piece to obtain a cross section of the target pole piece, and the cross section of the target pole piece is measured using a scanning electron microscope (SEM).

[0078] Select any first protrusions on the target pole pieces in 5 straight areas, measure the maximum height from the material layer surface of the target pole piece to a single first protrusion along the thickness direction of the target pole piece, and take the average value, which is the average height H1 of the multiple first protrusions.

[0079] Select any second protrusions on the target pole piece in 5 bending zones, measure the maximum height from the material layer surface of the target pole piece to a single second protrusion along the thickness direction of the target pole piece, and take the average value, which is the average height H2 of the multiple second protrusions.

[0080] Electrolyte component test:

[0081] The electrolyte components were tested using a gas chromatography-mass spectrometer (GC-MS, model: Agilent GC 7890A), and the external standard method was used to test the components to obtain the mass percentage of each component in the electrolyte.

[0082] Cycle performance test:

[0083] The lithium-ion batteries in the examples and comparative examples were subjected to a charge-discharge cycle test in an environment of 25°C. The lithium-ion batteries were charged to 4.5V at a constant current of 3.5C, charged to 0.05V at a constant voltage of 4.5V, left to stand for 10 minutes, and then discharged to 3V at a constant current of 0.5C. This was the first cycle, and the first cycle discharge capacity C1 was recorded. After 1000 cycles according to the above cycle process, the lithium-ion battery discharge capacity C 1000 , the cycle capacity retention rate at the 1000th cycle is calculated as an indicator for evaluating the cycle performance of lithium-ion batteries. The formula is shown below.

[0084] 1000cls capacity retention rate (%) = C 1000 / C1×100%.

[0085] When the 1000cls capacity retention rate is lower, it indicates that the cycle performance of the lithium-ion battery is worse; when the 1000cls capacity retention rate is higher, it indicates that the cycle performance of the lithium-ion battery is better.

[0086] Low temperature discharge performance test:

[0087] Take 5 lithium-ion batteries from each group, charge them in an environment of 25℃, and perform constant current and constant voltage charging at a charging current of 1C until the upper limit voltage. Then, place the fully charged lithium-ion batteries in an environment of 25℃ and -10℃ for 1h respectively, and then perform constant current discharge at a discharge current of 0.2C until the cut-off voltage, and obtain the discharge capacity D of the lithium-ion batteries respectively. R , D L Among them, the upper limit voltage of lithium-ion battery charging is 4.5V, and the discharge end voltage is 3V.

[0088] Low temperature capacity retention rate (%) = D L / D R ×100%.

[0089] When the low-temperature capacity retention rate is lower, it indicates that the low-temperature charge and discharge performance of the lithium-ion battery is worse; when the low-temperature capacity retention rate is higher, it indicates that the low-temperature charge and discharge performance of the lithium-ion battery is better.

[0090] High temperature storage performance:

[0091] Place the lithium-ion battery in a 25℃ constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25℃. Charge it to 4.5V at a constant current of 0.5C, and charge it to a current of 0.025C at a constant voltage of 4.5V. Record the thickness of the lithium-ion battery at this time as the initial thickness H0. Transfer the lithium-ion battery to an 85℃ constant temperature box and store it for 4 hours. Record the test thickness after 4 hours of storage as the storage thickness H1.

[0092] High temperature storage thickness expansion rate (%) = H1 / H0×100%-1.

[0093] The high-temperature storage thickness expansion rate is used to characterize the high-temperature storage performance of the lithium-ion battery; the smaller the high-temperature storage thickness expansion rate is, the better the high-temperature storage performance of the lithium-ion battery is, that is, the better the thermal safety performance of the lithium-ion battery is.

[0094] Example 1

[0095] <Preparation of positive electrode sheet>

[0096] The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent Super P, and the binder polyvinylidene fluoride were mixed in a mass ratio of 97.9:0.9:1.2, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75wt%, and the positive electrode slurry was obtained after vacuum stirring. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 120°C to obtain a positive electrode sheet with a single-sided coating of a positive electrode material layer. The coating weight of the positive electrode material layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a positive electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. The thickness of the single-sided positive electrode material layer is 42μm.

[0097] <Preparation of negative electrode sheet>

[0098] The negative electrode active material artificial graphite, the binder styrene butadiene rubber, and the conductive agent acetylene black were mixed in a mass ratio of 97.4:1.4:1.2, and deionized water was added as a solvent to prepare a slurry with a solid content of 45wt%. The negative electrode slurry was obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 54.5μm.

[0099] <Diaphragm>

[0100] A porous polyethylene film with a thickness of 7 μm (provided by Celgard Company) was used as a separator.

[0101] <Preparation of Electrolyte>

[0102] In a dry argon environment, cyclic carbonate ethylene carbonate (EC) and chain carbonate diethyl carbonate (DEC) which are liquid after heating are mixed in a mass ratio of 1:1 to obtain a non-aqueous solvent, and then propylene carbonate (PC), propyl propionate, sulfur oxide 1,3-propane sultone, nitrile additive malononitrile, fluorobenzene, and lithium salt LiPF6 are added to the non-aqueous solvent and mixed evenly to obtain an electrolyte. Among them, based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12%, the mass percentage of propylene carbonate A1 is 15%, the mass percentage of propyl propionate A2 is 35%, the mass percentage of sulfur oxide B is 1.2%, the mass percentage of nitrile compound C is 0.8%, and the mass percentage of fluorobenzene is 2%.

[0103] <Preparation of lithium-ion batteries>

[0104] The positive electrode sheet is determined to be the sheet with the protrusion, and the prepared positive electrode sheet, separator, negative electrode sheet, and separator are placed in order, and pre-wound, and the straight area and the bending area of ​​the electrode assembly are determined, and the first protrusion and the second protrusion are respectively set on the positive electrode sheet in the straight area and the bending area by a rubber roller and an embossing roller, and then the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 100°C, and the prepared electrolyte is injected, and the lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes. Among them, the average height H1 of the first protrusion is 12μm, the shape of the projection of the first protrusion on the positive electrode pole piece is a circle, and the diameter R1 of the maximum circumscribed circle of the outer contour of the orthographic projection of the first protrusion on the positive electrode pole piece is 1.2mm; the average height H2 of the second protrusion is 36μm, the shape of the projection of the second protrusion on the positive electrode pole piece is a circle, and the diameter R2 of the maximum circumscribed circle of the outer contour of the orthographic projection of the second protrusion on the positive electrode pole piece is 1.2mm; the value of H2 / H1 is 3.

[0105] Example 2 to Example 19

[0106] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0107] Example 20 to Example 34

[0108] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1. Among them, when the value of A1 and / or A2 in the electrolyte changes, the mass percentage of the non-aqueous solvent changes accordingly, and the ratio of each component in the non-aqueous solvent remains unchanged, unless the mass percentage of other substances except the non-aqueous solvent remains unchanged.

[0109] Example 35 to Example 42

[0110] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 23. Among them, when the value of B in the electrolyte changes, the mass percentage of the non-aqueous solvent changes accordingly, and the ratio of each component in the non-aqueous solvent remains unchanged, unless the mass percentage of other substances except the non-aqueous solvent remains unchanged.

[0111] Example 43 to Example 51

[0112] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 23. When the value of C in the electrolyte changes, the mass percentage of the non-aqueous solvent changes accordingly, and the ratio of each component in the non-aqueous solvent remains unchanged, unless the mass percentage of other substances except the non-aqueous solvent remains unchanged.

[0113] Example 52 to Example 58

[0114] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 23. Among them, when the value of D in the electrolyte changes, the mass percentage of the non-aqueous solvent changes accordingly, and the ratio of each component in the non-aqueous solvent remains unchanged, unless the mass percentage of other substances except the non-aqueous solvent remains unchanged.

[0115] Example 59 to Example 63

[0116] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1. Among them, when the values ​​of A1, A2, B, C and D in the electrolyte change, the mass percentage of the non-aqueous solvent changes accordingly, and the proportion of each component in the non-aqueous solvent remains unchanged, unless the mass percentage of other substances except the non-aqueous solvent remains unchanged.

[0117] Embodiment 64

[0118] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1. Among them, when the values ​​of A1 and A2 in the electrolyte change, the mass percentage of the non-aqueous solvent changes accordingly, and the ratio of each component in the non-aqueous solvent remains unchanged, unless the mass percentage of other substances except the non-aqueous solvent remains unchanged.

[0119] Comparative Example 1

[0120] Except that the first protrusion and the second protrusion are not provided on the positive electrode plate in <Preparation of lithium-ion battery>, the rest is the same as Example 1.

[0121] Comparative Example 2

[0122] Except that the second protrusion is not provided on the positive electrode sheet in the bending area in <Preparation of Lithium-ion Battery>, the rest is the same as Example 1.

[0123] Comparative Example 3

[0124] Except that the first protrusion is not provided on the positive electrode sheet in the straight area in <Preparation of Lithium Ion Battery>, the rest is the same as Example 1.

[0125] Comparative Examples 4 to 8

[0126] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0127] Comparative Example 9

[0128] Except that the first protrusion and the second protrusion are not provided on the positive electrode plate in <Preparation of lithium-ion battery>, and the electrolyte is prepared according to the following steps, the rest is the same as Example 1.

[0129] <Preparation of Electrolyte>

[0130] In a dry argon environment, cyclic carbonate ethylene carbonate (EC) and chain carbonate diethyl carbonate (DEC) are mixed in a mass ratio of 1:1 to obtain a non-aqueous solvent, and then lithium salt LiPF6 is added to the non-aqueous solvent and mixed evenly to obtain an electrolyte. The mass percentage of lithium salt LiPF6 based on the mass of the electrolyte is 12%.

[0131] Comparative Example 10

[0132] Except that the electrolyte in <Preparation of Electrolyte> does not contain sulfur oxide compounds, the mass percentage of the non-aqueous solvent changes accordingly, and the proportion of each component in the non-aqueous solvent remains unchanged. The rest is the same as Example 23, except that the mass percentage of other substances except the non-aqueous solvent remains unchanged.

[0133] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.

[0134] Table 1

[0135] Note: “ / ” in Table 1 indicates no relevant preparation parameters or result parameters.

[0136] It can be seen from Examples 1 to 64 and Comparative Examples 1 to 10 that by respectively providing the first protrusion and the second protrusion on the pole pieces in the straight area and the bent area, and regulating the value of H2 / H1 and the value of H1 within the scope of the present application, when the electrolyte contains sulfur oxides, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are improved, and the high-temperature storage thickness expansion rate is reduced, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance and high-temperature storage performance. In Comparative Examples 1 and 9, the first protrusion and the second protrusion are not provided on the pole piece, and the electrolyte of Comparative Examples 9 and 10 does not contain sulfur oxides; in Comparative Example 2, the first protrusion is provided only on the pole piece in the straight area; in Comparative Example 3, the second protrusion is provided only on the pole piece in the bending area; the value of H2 / H1 in Comparative Examples 4 to 5 is not within the scope of the present application; the value of H1 in Comparative Examples 6 to 7 is not within the scope of the present application; the value of H2 / H1 and the value of H1 in Comparative Example 8 are not within the scope of the present application; the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery in Comparative Examples 1 to 10 are low, and the high-temperature storage thickness expansion rate is high. In Examples 1 to 64, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance and high-temperature storage performance.

[0137] The value of H2 usually affects the cycle performance, low-temperature discharge performance and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 1 to 14 that when the value of H2 is within the range of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance and high-temperature storage performance.

[0138] The values ​​of R1 and R2 usually affect the cycle performance, low-temperature discharge performance and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 1 and 15 to 19 that when the values ​​of R1 and R2 are within the range of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance and high-temperature storage performance.

[0139] The values ​​of A1 and A2 usually affect the cycle performance, low-temperature discharge performance and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 1, 20 to 34, and 64 that when the values ​​of A1 and A2 are within the range of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance and high-temperature storage performance.

[0140] Different combinations of the values ​​of A1+A2 and H2 usually affect the cycle performance, low-temperature discharge performance, and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 20, 31, 59 to 63 that when the values ​​of A1+A2 and H2 are different combinations within the scope of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance, and high-temperature storage performance.

[0141] The type of sulfur oxide and the value of B usually affect the cycle performance, low temperature discharge performance and high temperature storage performance of lithium ion batteries. It can be seen from Examples 23, 35 to 42 that when the type of sulfur oxide and the value of B are within the range of this application, the 1000cls capacity retention rate and low temperature capacity retention rate of the lithium ion battery are high, and the high temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium ion battery has good cycle performance, low temperature discharge performance and high temperature storage performance.

[0142] Different combinations of B values ​​and H2 values ​​usually affect the cycle performance, low-temperature discharge performance, and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 20, 31, 59 to 63 that when the different combinations of B values ​​and H2 values ​​are within the scope of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance, and high-temperature storage performance.

[0143] The type of nitrile compound and the value of C usually affect the cycle performance, low-temperature discharge performance and high-temperature storage performance of the lithium-ion battery. It can be seen from Examples 23, 43 to 51 that when the type of nitrile compound and the value of C are within the scope of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance and high-temperature storage performance.

[0144] Different combinations of C values ​​and H2 values ​​usually affect the cycle performance, low-temperature discharge performance, and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 20, 31, 59 to 63 that when the different combinations of B values ​​and H2 values ​​are within the scope of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance, and high-temperature storage performance.

[0145] The value of D usually affects the cycle performance, low-temperature discharge performance and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 23 and 52 to 58 that when the value of D is within the range of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance and high-temperature storage performance.

[0146] Different combinations of D values ​​and H2 values ​​usually affect the cycle performance, low-temperature discharge performance, and high-temperature storage performance of lithium-ion batteries. It can be seen from Examples 20, 31, 59 to 63 that when the different combinations of D values ​​and H2 values ​​are within the scope of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance, and high-temperature storage performance.

[0147] Different combinations of electrolytes usually affect the cycle performance, low-temperature discharge performance, and high-temperature storage performance of lithium-ion batteries. It can be seen from Example 1 and Example 20 to Example 64 that when different combinations of electrolytes are within the scope of this application, the 1000cls capacity retention rate and low-temperature capacity retention rate of the lithium-ion battery are high, and the high-temperature storage thickness expansion rate is low, indicating that the electrolyte has good wetting performance on the electrode assembly, and the lithium-ion battery has good cycle performance, low-temperature discharge performance, and high-temperature storage performance.

[0148] It is noted that, in this article, relational terms such as first and second, etc. are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises", or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, or article that includes a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also includes elements that are inherent to such process, method, or article.

[0149] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0150] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A secondary battery, characterized in that: An electrode assembly and an electrolyte comprising a winding structure, the electrode assembly comprising a pole piece, the electrode assembly comprising a straight region and a bent region, a plurality of first protrusions are arranged on the pole piece in the straight region, a plurality of second protrusions are arranged on the pole piece in the bent region, along the thickness direction of the pole piece, the average height of the plurality of first protrusions is H1 μm, the average height of the plurality of second protrusions is H2 μm, 1.5≤H2 / H1≤5, 5≤H1≤40; the electrolyte comprises a sulfur oxide compound, based on the mass of the electrolyte, the mass percentage of the sulfur oxide compound is B, and the secondary battery satisfies one of the following conditions: (1) 0.5%≤B<2%, 20≤H2<60; (2) 2%≤B≤4%, 60≤H2≤80.

2. The secondary battery according to claim 1, characterized in that: 2≤H2 / H1≤4; and / or, 5≤H1≤20.

3. The secondary battery according to claim 1, characterized in that: Along the thickness direction of the pole piece, the diameter of the maximum circumscribed circle of the outer contour of the orthographic projection of the first protrusion on the pole piece is R1 mm, and the diameter of the maximum circumscribed circle of the outer contour of the orthographic projection of the second protrusion on the pole piece is R2 mm, 0.3≤R1≤10, 0.3≤R2≤10.

4. The secondary battery according to claim 1, characterized in that: Along the thickness direction of the pole piece, the first protrusion and the second protrusion are located on the same side of the pole piece; or, the first protrusion and the second protrusion are located on different sides of the pole piece.

5. The secondary battery according to claim 1, characterized in that: The pole piece is a positive pole piece.

6. The secondary battery according to claim 1, characterized in that: The electrolyte includes propylene carbonate and propyl propionate. Based on the mass of the electrolyte, the mass percentage of propylene carbonate is A1, the mass percentage of propyl propionate is A2, 2.5%≤A1≤15%, 20%≤A2≤40%.

7. The secondary battery according to claim 6, characterized in that: 4%≤A1≤12%; and / or, 30%≤A2≤40%.

8. The secondary battery according to claim 6, characterized in that: Meet one of the following conditions: (1) 22.5%≤A1+A2<43%, 20≤H2<60; (2) 43%≤A1+A2≤55%, 60≤H2≤80.

9. The secondary battery according to claim 1, characterized in that: The sulfur oxide compound includes at least one of 1,3-propane sultone, disulfate or vinyl sulfate.

10. The secondary battery according to claim 9, characterized in that: The sulfur oxide compound includes 1,3-propane sultone; and / or, 0.6%≤B≤2.8%.

11. The secondary battery according to claim 1, characterized in that: The electrolyte includes a nitrile additive, and the nitrile additive includes at least one of malononitrile, succinonitrile, adiponitrile, terephthalonitrile, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether or diethylene glycol di(2-cyanoethyl) ether. Based on the mass of the electrolyte, the mass percentage of the nitrile additive is C, 0.8%≤C≤4.5%.

12. The secondary battery according to claim 11, characterized in that: Meet one of the following conditions: (1) 0.8%≤C<3%, 20≤H2<60; (2) 3%≤C≤4.5%, 60≤H2≤80.

13. The secondary battery according to claim 1, characterized in that: The electrolyte further includes fluorobenzene. Based on the mass of the electrolyte, the mass percentage of fluorobenzene is D, and 2%≤D≤8%.

14. The secondary battery according to claim 13, characterized in that: Meet one of the following conditions: (1) 2%≤D<5%, 20≤H2<60; (2) 5%≤D≤8%, 60≤H2≤80.

15. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Lithium ion battery and electrolyte thereof

    CN103107355A

  • Non-aqueous electrolyte and lithium ion battery containing same

    CN114520371A

  • Electrode assembly and battery

    CN117638254A

  • Power storage element and power storage device

    JP2015092460A

  • Electrolyte solution and battery

    WO2024222383A1

Cited By

  • Composite current collector, preparation method thereof and secondary battery

    CN120072953A